The Influence of Social-Economic Condition of People to Landuse Change and the Influence of Landuse Change to Runoff at Bodri Watershed, Kendal - Laviati, Riani; Anna, Alif Noor; Suharjo, Suharjo (Universitas Muhammadiyah Surakarta, 2003)
This study is carried out in chacthment area of Bodri. The goals of this study are to kno the influence of economic social condition of population on the change of the kind of landuse and the influence of the change of the kind of landuse on the run-off area. This study uses survey method. The collected data are the economic social data of the population and the physical condition data in the research area. The result of the study shows that the economic social condition of the population in chatchment area of Bodri influences on the decrease of landuse. The decrease in landuse is 22.27% which used settlement, dry land cultivation (3.14%), yard (1.07%), plantation (0.44%), wet land cultivation (2.28%), embankment (0.25%), street and others (6.73%). The decrease in landuse causes peak discharge of Hydrograph in 1997, 1999, 2000, and 2001 increases respectively 87.32 m/second, 101.26 m/second, 58.37 m/second, 89.82 m/second, with each volume of direct flow 7.123.392 m, 6.011.604 m, 11.784.672 m, and 9.459.954 m. The run-off coefficient in 1992, 1997, 1999, 2000, and 2001 increase 7.7%, 13%, 19.8%, 23.2%, and 27.03%, with coefficient of annual flow 46.98%, 72%, 55.21%, 61,79%, and 75.55%. The increasing of the run-off coeficient and annual flow describes that the ratio both the discharge of maximum and minimum monthly flow becomes bigger. It means that in rainy season it will be flood immediately and in dry season it will be drought easily.